Transferring Knowledge and Expertise to Legal Officers on How to Prosecute Criminals Relating to Witchcraft - Mahyuddin, Ismail; Mansor, Sulaiman; Zulfakar, Ramlee; Mohd Syahrizal Syah, Zakaria (Knowledge Transfer Centre, USM, 2016)
Witchcraft has been already known to cause harm to humans. In fact, the 33rd Fatwa Committee of the National Council for Islamic Religious Affairs of Malaysia ruled that the authorities must provide legal provisions to punish witches. Disappointingly, after 20 years, the law has not yet been enacted. This is due to the failure of the related parties to understand the nature of witchcraft itself as well as the difficulty of proof-finding in court. Thus, this transfer program aims to disclose the new findings of research on witchcraft law exclusively to government officers who involve in drafting, prosecuting and executing the law. The program applied several methods including thorough discussion, case studies, simulations and scene investigation in 5 series of workshop. In this program, four major issues, namely the legal provisions, the legal procedures, the expert recognition and the legal evidences are thoroughly discussed. As a result, a set of proposal which contains a comprehensive draft of the provisions, the S.O.P. For investigation, arrest, search and seizure process, and the types of admissible evidence is to be brought to the authorities. This program successfully convinced the participants that offenses relating to witchcraft can be overcome through legal mechanisms